Representações de alunos do ensino médio sobre o ensino-aprendizagem de inglês: um estudo de caso na escola pública em Coari (AM) - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Social Representations have been increasingly used in studies in various fields and English teaching and learning has been no different. The general aim of this research was to investigate High School students’ representations about the teaching-learning of English in a public school in Coari – Amazonas. The specific objectives were to identify and understand how English teaching-learning takes place in public schools in the interior of Amazonas in the light of student’s representations and, in accordance with these representations, to analyze possibilities for making the teaching-learning of English more effective in public schools. The theoretical contribution of this study was grounded on the theory of social representations, and it was based on Jodelet (2001), Moscovici (1978) and authors who address the subject in Applied Linguistics, such as Celani and Magalhães (2002) and Farr (2002). A brief history of the teaching-learning of English in Brazil, with focus on Amazonas, based on Leffa (2016), Monteiro (2009; 2014), Paiva (2001; 2003), Vale (2014) and others is also presented. Some considerations about the teaching-learning of English in Brazilian public schools are presented, based on the British Council (2019) and the guidelines proposed in the BNCC (Brazil, 2018). As far as teaching-learning of English in High School, it was used Marzari and Gehres (2015), Gasparini (2005), Eidelwein and Motin (2021), Brazil (2018) and Amazonas (2019) as references. This research is a study in the field of Applied Linguistics, and it takes a qualitative approach based on Fraser and Godim (2004) and Minayo (2002) and it was configured as a case study, based on Yin (2005), Stake (2003) and André (2013). The context was a full-time public High School located in the interior of Amazonas and the research instruments were two questionnaires, a profile and an investigative questionnaire applied to ten 3rd grade High School students. Bardin's Analysis (2016) was used to analyze the data and the results showed that the teaching-learning is carried out using methodologies that the participants considered to be “practical, active and diversified” and using materials such as the blackboard, the textbook and the data show, the last one is only possible for teachers who have invested in the purchase of this object, which reveals the teachers' financial investment in the acquisition of teaching materials and the lack of these materials not only in teaching-learning of English, but in the context of the full-time school in question. The study also revealed that teachers prepare and adapt materials involving the students' context. The students' main difficulties are pronunciation and grammar rules. To make the teaching-learning of English more effective, the data showed that more “practical and dynamic activities” are needed, an increase in the number of hours of English classes, more interest from students, a friendly relationship between teacher and student in English classes and investment in initial and ongoing teacher training.
High school students' representations of English teaching and learning: a case study in a public school in Coari (AM)
Keywords: Linguagem e línguas - Estudo e ensino; Professores de línguas - Formação; Língua inglesa - Estudo e ensino; LINGUISTICA, LETRAS E ARTES; Representações; Ensino-aprendizagem de inglês; Ensino médio; Escola pública; Formação de professores